Targeted Protein Delivery: Supramolecular Toxin Complexes for Targeted Pharmacological Modulation of Polymorphonuclear Leukocyte Functions (Adv. Healthcare Mater. 17/2019). Issue 17 (5th September 2019) - Heck, Astrid Johanna; Ostertag, Theresa; Schnell, Leonie; Fischer, Stephan; Agrawalla, Bikram Keshari; Winterwerber, Pia; Wirsching, Eva; Fauler, Michael; Frick, Manfred; Kuan, Seah Ling; Weil, Tanja; Barth, Holger
Abstract : Excessive recruitment of polymorphonuclear neutrophils (PMNs) into injured tissues after traumatic injuries can be highly detrimental to patients and remains a significant source of morbidity and mortality. In article number1900665 by Seah Ling Kuan, Tanja Weil, Holger Barth, and co‐workers, the authors develop supramolecular protein complexes for pharmacological modulation of PMNs. In this way, a novel therapeutic approach is formulated by fusing PMN‐binding peptides to a Rho‐inhibiting enzyme on a supramolecular platform.